The Role of Organizational Culture in KnowledgeManagement in Small Companies - Kaja Prystupa (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Organizational culture is an important factor influencing knowledge management processes in small companies. Small entities usually have limited resources, both human and financial, to be able to develop advanced knowledge management systems. However, little research has been done so far to investigate the characteristics of organizational culture in small companies, in terms of knowledge management processes. Therefore, the aim of this research is the examination of organizational culture in small Polish companies with the application of a symbolic-interpretive perspective.